Housing Speculation and Investment in Children’s Education: Evidence from House Purchase Restrictions in China - Niu, Geng; Xiang, Xuefeng; Yang, Liuming; Zhou, Yang (Journal of Financial and Quantitative Analysis, 2026)
Abstract Housing and human capital represent two major forms of household wealth. This article investigates the potential for housing speculation to crowd out household investment in children’s education, an endeavor that only pays off in the long run. To address endogeneity concerns, we exploit the unintended spillover effect of staggered house purchase restrictions (HPR) in China. Using a difference-in-differences approach, we find that HPR reduce educational investment of households in nearby unregulated cities. We also provide evidence consistent with a housing speculation channel. These findings shed new light on the socioeconomic consequences of housing market booms.